2018
DOI: 10.1016/j.ijid.2017.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam resistance among Enterobacteriaceae in Cambodia: The four-year itch

Abstract: Although antibiotics are too often used inappropriately in Cambodia, published data on antimicrobial resistance in this country are scarce. Epidemic dissemination and the transfer of resistance genes to other bacterial species put the population at risk. The aim of this study was to evaluate the frequency and characteristics of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae (ESBL-E) isolated in consecutive samples tested at Institut Pasteur du Cambodge over a 4-year period (2012-2015). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Despite this relatively low percentage of isolation of ESBL-producers, the selected strains were characterized by a high degree of resistance to antibiotics of other pharmaceutical groups, and primarily to macrolides -erythromycin and azithromycin, as well as to co-trimoxazole and fosfomicin. The results, obtained in the present research, prove the data of other authors, who showed that the ESBLproducing strains of enterobacteria, isolated from the clinical material of the patients with various infectious-inflammatory diseases of the urogenital tract, are characterized by multi-resistance [2,5,6]. Thus, it was shown by P. Aminul et al [2] that in addition to resistance to β-lactams, clinical bacteria strains of family Enterobacteriaceae showed co-resistance to fluoroquinolones and aminoglycosides, according to the data of А. Ben Ashur with the co-authors [4] -to nitrofurans and tetracyclines.…”
Section: т a B L Esupporting
confidence: 90%
“…Despite this relatively low percentage of isolation of ESBL-producers, the selected strains were characterized by a high degree of resistance to antibiotics of other pharmaceutical groups, and primarily to macrolides -erythromycin and azithromycin, as well as to co-trimoxazole and fosfomicin. The results, obtained in the present research, prove the data of other authors, who showed that the ESBLproducing strains of enterobacteria, isolated from the clinical material of the patients with various infectious-inflammatory diseases of the urogenital tract, are characterized by multi-resistance [2,5,6]. Thus, it was shown by P. Aminul et al [2] that in addition to resistance to β-lactams, clinical bacteria strains of family Enterobacteriaceae showed co-resistance to fluoroquinolones and aminoglycosides, according to the data of А. Ben Ashur with the co-authors [4] -to nitrofurans and tetracyclines.…”
Section: т a B L Esupporting
confidence: 90%
“…To date, there are no published reports of CPE/K in humans or livestock in Cambodia or of community carriage of ESCE/K in Cambodia. However, ESCE/K isolates have been detected as causative pathogens in Cambodian patients (Caron et al, ; Emary et al, ; Moore et al, ; Rammaert et al, ; Vlieghe et al, ). Genetic characterization of ESBL‐producing E. coli isolates in bloodstream infections in Cambodia revealed that 96% were of CTX‐M‐type, mainly bla CTX‐M‐15 and bla CTX‐M‐14 (Vlieghe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from 2004/5 and 2007–2011 identified ESC resistance in 36–44% of urinary tract infection isolates [10, 11]. Recent data from a Cambodian reference laboratory suggests that the prevalence of ESBL resistance amongst Enterobacteriaceae isolated from hospitalised and community-based patients increased from 23.8% in 2012 to 38.4% in 2015 [12]. The gastrointestinal colonisation prevalence of ESC-resistant (ESC-R) E. coli and K. pneumoniae in Cambodia has previously only been investigated in hospitalised neonates [13], where on initial admission 21% were colonised with ESC-R E. coli (ESC-R-EC) and 33% with ESC-R K. pneumoniae (ESC-R-KP), increasing to 34 and 42% respectively on repeat admissions.…”
Section: Introductionmentioning
confidence: 99%